Analysis of school children’s height from two different socioeconomic status in rural area of Wardha District of Maharashtra, India - Tote, Sachin D.; Tote, Darshana S.; Gajbe, Ujwal (International Journal of Advances in Medicine, 2017)
Background: Anthropometry is widely recognized as one of the useful technique to assess the growth and nutritional status of an individual as population. The present study was carried out with the aim to study the growth parameter of the school going children and to find association of socioeconomic status and height. Methods: School children from age 6 to 14 years are examine for weight. There socioeconomic status is decided on the basis of ration card. A total 1520 school children aged 6 to 14 years were randomly selected from the 5 different schools. Results: Significant difference between the height was found among the upper and lower socioeconomic groups children. Conclusions: Statistically significant difference is found between two socioeconomic groups in the age group of 6, 7, 10, and 14 years of male and 6, 8, 11, and 12 years in female between two socioeconomic groups.